Design and Assessment of a 2.5-Gb/s Optical Wireless Transmission System for High Energy Physics - W. Ali; G. Cossu; A. Sturniolo; R. DellOrso; A. Messineo; F. Palla; E. Ciaramella (IEEE Photonics Journal)
We designed, realized, and tested a 2.5-Gb/s optical wireless communication (OWC) system prototype, that should be employed in high energy physics (HEP) experiments, such as the compact muon solenoid (CMS). The system consists of off-the-shelf components, mainly a vertical cavity surface emitting laser (VCSEL) and a PIN photodiode with a proper ball lens. Since it should be used to transmit data among particle sensors in neighboring rings of the CMS, its target distance is 10 cm. Its most attractive feature is that it does not require a (complex) active tracking system because its measured tolerance to misalignment is around $±$ 1 mm (at $10^{-12}$ bit error rate). We also report the X-rays irradiation tests of all components (Quartz lens, VCSEL, and PIN photodiode): None of them showed any degradation up till 238-Mrad (Si) dose. These results indicate that the designed OWC can be a viable solution for future HEP experiments.